Automated abdominal aortic calcification scoring from vertebral fracture assessment images and fall-associated hospitalisations: the Manitoba Bone Mineral Density Registry - Marc Sim; Abadi K. Gebre; Jack Dalla Via; Siobhan Reid; Mohammad Jafari Jozani; Douglas Kimelman; Barret A. Monchka; Syed Zulqarnain Gilani; Zaid Ilyas; Cassandra Smith; David Suter; John T. Schousboe; et al. (GeroScience, 2025)
Abdominal aortic calcification (AAC), a subclinical measure of cardiovascular disease (CVD) that can be assessed on vertebral fracture assessment (VFA) images during osteoporosis screening, is reported to be a falls risk factor. A limitation to incorporating AAC clinically is that its scoring requires trained experts and is time-consuming. We examined if our machine learning (ML) algorithm for AAC (ML-AAC24) is associated with a higher fall-associated hospitalisation risk in the Manitoba Bone Mineral Density (BMD) Registry. A total of 8565 individuals (94.0% female, age 75.7 ± 6.8 years) who had a BMD and VFA image from DXA between February 2010 and December 2017 were included. ML-AAC24 was categorised based on established categories (ML-AAC24 = low < 2; moderate 2 to < 6; high ≥ 6). Cox proportional hazards models assessed the relationship between ML-AAC24 categories and incident fall-associated hospitalisations obtained from linked health records (mean ± SD follow-up, 3.9 ± 2.2 years). Individuals with moderate (9.6%) and high ML-AAC24 (11.7%) had a greater proportion of fall-associated hospitalisations, compared to those with low ML-AAC24 (6.0%). In age and sex-adjusted models, compared to low ML-AAC24, moderate (HR 1.49, 95% CI 1.24–1.79) and high ML-AAC24 (HR 1.89, 95% CI 1.56–2.28) were associated with greater hazards for a fall-associated hospitalisation. Results were comparable (HR 1.37, 95% CI 1.13–1.65 and HR 1.60, 95% CI 1.31–1.95, respectively) after multivariable adjustment, including prior falls and CVD, as well as medication use. Integrating ML-AAC24 into bone density machine software to identify high risk individuals would opportunistically provide important information on fall and cardiovascular disease risk to clinicians for evaluation and intervention.

Changes in cardiovascular health and white matter integrity with aerobic exercise, cognitive and combined training in physically inactive healthy late-middle-aged adults: the “Projecte Moviment” randomized controlled trial - Francesca Roig-Coll; Alba Castells-Sánchez; Gemma Monté-Rubio; Rosalía Dacosta-Aguayo; Noemí Lamonja-Vicente; Pere Torán-Monserrat; Guillem Pere; Alberto García-Molina; José Maria Tormos; Maria Teresa Alzamora; Dimitriadis Stavros; Marta Sánchez-Ceron; et al. (European Journal of Applied Physiology, 2024)
Introduction This is a 12-weeks randomized controlled trial examining the effects of aerobic exercise (AE), computerized cognitive training (CCT) and their combination (COMB). We aim to investigate their impact on cardiovascular health and white matter (WM) integrity and how they contribute to the cognitive benefits. Methods 109 participants were recruited and 82 (62% female; age = 58.38 ± 5.47) finished the intervention with > 80% adherence. We report changes in cardiovascular risk factors and WM integrity (fractional anisotropy (FA); mean diffusivity (MD)), how they might be related to changes in physical activity, age and sex, and their potential role as mediators in cognitive improvements. Results A decrease in BMI (SMD = − 0.32, p = 0.039), waist circumference (SMD = − 0.42, p = 0.003) and diastolic blood pressure (DBP) (SMD = − 0.42, p = 0.006) in the AE group and a decrease in BMI (SMD = − 0.34, p = 0.031) and DBP (SMD = − 0.32, p = 0.034) in the COMB group compared to the waitlist control group was observed. We also found decreased global MD in the CCT group (SMD = − 0.34; p = 0.032) and significant intervention-related changes in FA and MD in the frontal and temporal lobes in the COMB group. Conclusions We found changes in anthropometric measures that suggest initial benefits on cardiovascular health after only 12 weeks of AE and changes in WM microstructure in the CCT and COMB groups. These results add evidence of the clinical relevance of lifestyle interventions and the potential benefits when combining them. Clinical Trial Registration ClinicalTrials.gov NCT031123900.